Learning with Nature in Malaysia: Methods of Incorporating Nature in Kindergarten Outdoor Physical Environments - Shaari, Mariam Felani; Nazri, Batrisyia (Online Journal for TVET Practitioners, 2023)
Learning with nature is increasingly popular in Malaysia. However, there are challenges when designing kindergarten outdoor physical environments to assist learning with nature in Malaysia. Previous studies have looked into the types of necessary nature interaction and spaces needed for learning with nature. However, there is a gap in understanding the factors influencing the methods to include nature in the kindergarten outdoor areas. This research aims to investigate the methods of incorporating nature in the outdoor physical environment of kindergartens to facilitate learning with nature. This research is a multiple case study using maximum variation sampling. The main findings suggest that each school’s design is unique as their curriculums and philosophy are different, and the way children interact with nature depends on it. Gibson’s Theory of Affordances, which is when the environment and surroundings allow for the interaction we intended, can help design kindergarten outdoor areas to cater to the curriculum. Integrating nature and man-made materials in the design can create a conducive environment for learning with nature. External factors namely the size of available outdoor areas, terrain conditions, and others will influence how nature is incorporated in the design.